THE ERRORS LINGUISTIC OF THE MASTER'S STUDENTS IN THE FACULTIES OF EDUCATION FOR HUMAN AND SPORT SCIENCES AT WRITING SCIENTIFIC RESEARCH - Dr. Mohammed Abbas Mohammed , Dr. Dihya Uweed Harbi Al Arnoosy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims is to identify the error linguistic (spelling, grammatical and morphological) of the master students in the faculties of education of human sciences and sports in the writing of scientific research. The researchers tried to limit some of these linguistic errors and determine their types in writing scientific thesis’s because it the mirror of the language aspect. In order to achieve the goal of the research, the researchers chose several different messages and sections and studied and revealed the frequency of errors and the most common in these messages. In the context of the discovery of linguistic errors, researchers found that the Department of Physical Education issued a total of errors, with the number of linguistic errors (662) error in the total errors and then the history section and finally the geographical of the total errors. (1743) linguistic errors, and these errors are not in form or in the formulation and structures or in the sense of words or derivation, where they tried to identify the reasons that led to those errors and then concluded the researchers many recommendations and some suggestions.